2017
DOI: 10.17221/355/2015-agricecon
|View full text |Cite
|
Sign up to set email alerts
|

The Sweezy model of price competition among private labels of chain stores

Abstract: Svoboda R., Kopecka L. (2017): Th e Sweezy model of price competition among private labels of chain stores. Agric. Econ. -Czech, 63: 299-307.Abstract: Th e aim of the paper is to verify and explain the actual eff ects of the Sweezy oligopoly model and its eventual impact on the consumer demand and the structure of the food supply of chain stores. Th e methodology of the paper is based on a comparative analysis of the structure of commodities of chain stores in the Czech Republic in terms of consumer demand and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…In particular, the effect of perceived risk on purchase intention of PL seems to be a key variable in the research theme of perceived PL characteristics (Riboldazzi et al, 2021). As in a study where Easterners were found to have stronger risk aversion than Westerners, this may also correlate with the fact that Asian buyers tend to seek commodities that present less risk (Svoboda and Kopecka, 2017).…”
Section: Perceived Riskmentioning
confidence: 95%
“…In particular, the effect of perceived risk on purchase intention of PL seems to be a key variable in the research theme of perceived PL characteristics (Riboldazzi et al, 2021). As in a study where Easterners were found to have stronger risk aversion than Westerners, this may also correlate with the fact that Asian buyers tend to seek commodities that present less risk (Svoboda and Kopecka, 2017).…”
Section: Perceived Riskmentioning
confidence: 95%
“…(Kelting, et al, 2017) The importance of defining the factors that determine consumers' attitudes to private label products is obvious and that is the reason why the issue is solved at the level of individual econo-mies. The level of private label products on the Australian market is the research aim of Cleanthous et al (2011); African markets is the research object of Wyma et al (2014); the attitudes of French consumers are presented by Mannot et al, (2015); Kakkos et al (2015) identify the main reasons for the purchase of private products by Greek consumers; Thai shopping decision making of private products is processed in Thanasuta research (2015); Czech consumers' perception of the private label products is described by Kocisiarova & Nagy (2015) and Svoboda & Kopecka (2017).…”
Section: Theoretical Backgroundmentioning
confidence: 99%